FERMENTATION OF KIVUGUTO, A RWANDESE TRADITIONAL MILK: SELECTION OF MICROBES FOR A STARTER CULTURE (Sciences & Technologie. C, Biotechnologies, 2012)
A total of 390 bacterial strains were isolated from four kivuguto samples. Isolates were screened by phenotypic methods and molecular techniques using the PCR and sequencing of 16S rDNA and/or 16S-23S rDNA intergenic transcribed spacer (ITS) region. The rate of milk acidification and ability to grow under extreme environmental conditions were also examined for pre-selected isolates. Fermentation assays with mixed strains were performed to identify microbial formulations that produced milk similar to kivuguto. Such formulated milk was stored at 4°C on 24 days for shelf-life analysis to detect any organoleptic defect. Bacteria identified in kivuguto included Lactococcus lactis (strains CWB-B1466 and CWBI-B1469) and Leuconostoc mesenteroides subsp. mesenteroides (strains CWBI-B1467 and CWBI-B1465) and Leuconostoc pseudomesenteroides (T) (NRIC177) (strains CWBI-B1468, CWBI-B1470 and CWBI-B1471). One Leuconostoc sp. grew at low pH 2.5, in high sodium chloride concentration (up to 6.5%) and was resistant to heat (55°C). Fermentation experiments showed that kivuguto coagulates in 8 hours at 30°C. Three milk formulations produced using mixed strains gave good results. The best-tasting and longest shelf-life (35 days) kivuguto was produced by a mixture of two Leuconostoc spp. and Lactococcus lactis. These strains give kivuguto its characteristic properties.